2021
DOI: 10.21037/atm-21-2944
|View full text |Cite
|
Sign up to set email alerts
|

Triptolide reverses epithelial-mesenchymal transition in glioma cells via inducing autophagy

Abstract: Background: To observe the effects of triptolide (TP) on the proliferation, migration, invasion, and epithelial-mesenchymal transition (EMT) of glioma cells, and to explore the possible mechanisms of phenotypic changes in EMT.Methods: The U87 and U251 glioma cell lines were treated TP. The Cell Counting Kit-8 (CCK-8) method was used to detect the half-maximal inhibitory concentration (IC 50 ) of TP in these two cell lines and the inhibition of cell proliferation at the IC 50 concentration. The wound-healing ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…At present, the main treatment for glioma is surgery combined with high-precision chemoradiotherapy and tumor treatment field (TTF) ( 3 ). Glioma has made advances in chemotherapy and surgery, but overall survival (OS) has not increased significantly, and the challenges of rapid spread, molecular heterogeneity, and drug delivery across the blood–brain barrier limit the therapy effectiveness ( 4 , 5 ). As immunotherapy is gradually applied to malignant tumors, the study of the tumor microenvironment and tumor–host interaction is helpful to develop new therapeutic strategies, which is an important direction to explore potential therapies for glioma ( 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…At present, the main treatment for glioma is surgery combined with high-precision chemoradiotherapy and tumor treatment field (TTF) ( 3 ). Glioma has made advances in chemotherapy and surgery, but overall survival (OS) has not increased significantly, and the challenges of rapid spread, molecular heterogeneity, and drug delivery across the blood–brain barrier limit the therapy effectiveness ( 4 , 5 ). As immunotherapy is gradually applied to malignant tumors, the study of the tumor microenvironment and tumor–host interaction is helpful to develop new therapeutic strategies, which is an important direction to explore potential therapies for glioma ( 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…Autophagy is a major process that contributes to the maintenance of intracellular energy metabolism and self‐survival 18 . Recently, it has been demonstrated that autophagy and EMT are tightly correlated in regulating tumorigenesis and tumour progression 19,20 . During the initial stage of tumour, autophagy suppresses cancer invasion and metastasis by selectively degrading important signalling molecules in the EMT process 19 .…”
Section: Discussionmentioning
confidence: 99%
“…18 Recently, it has been demonstrated that autophagy and EMT are tightly correlated in regulating tumorigenesis and tumour progression. 19,20 During the initial stage of tumour, autophagy suppresses cancer invasion and metastasis by selectively degrading important signalling molecules in the EMT process. 19 In contrast, during the process of tumour metastasis and diffusion, cancer cells need to activate autophagy to obtain sufficient energy and promote EMT.…”
Section: Discussionmentioning
confidence: 99%
“…The tumor tissues were dissected and collected. Pathological examination and SABER-FISH were used to assess the expression of EMT related antibodies and the location of lncRNA-ATB in tissues [ 13 , 14 ].…”
Section: Methodsmentioning
confidence: 99%